Green Innovation and firm Performance: An Empirical Study of China's Power Industry - Xiaoyuan Zhang; Shenglian Wang; Nurul Azlin Azmi; RAJA ADZRIN RAJA AHMAD (Information Management and Business Review, 2024)
With China’s goal of achieving "carbon peak and neutrality”, green innovation has become an inevitable choice to accomplish the dual objective of ecological protection and economic growth. The objective of this study is to examine whether green innovation can contribute to enhancing firm performance. Specifically, this study empirically investigates the relationship between green innovation and firm performance by analyzing a sample of listed firms in China's A-share power industry from 2009 to 2022. By using panel fixed effect regression, this study found that green innovation markedly and positively enhances the firm's current performance. Furthermore, this paper tested the effect of green innovation on the firm's future performance, which is positive and greater than the effect on the current performance. Through data support spanning 14 years, this study verifies the theoretical hypothesis that green innovation can substantially enhance firm performance in the power industry. This not only deepens the understanding of how green innovation affects firm performance but also offers empirical evidence to support the further implementation and advancement of green innovation within the power industry. This study only uses a sample of a single industry, so the conclusions of this study do not have explanatory power for firms in other industries.